The duct of von Ebner’s glands is a source of Sox10+ taste bud progenitors and susceptible to pathogen infections - Yu, Wenxin; Kastriti, Maria Eleni; Ishan, Mohamed; Choudhary, Saurav Kumar; Rashid, Md Mamunur; Kramer, Naomi; Do, Hy Gia Truong; Wang, Zhonghou; Xu, Ting; Schwabe, Robert F.; Ye, Kaixiong; Adameyko, Igor; et al. (Frontiers in Cell and Developmental Biology, 2024)
We have recently demonstrated that Sox10-expressing (Sox10 + ) cells give rise to mainly type-III neuronal taste bud cells that are responsible for sour and salt taste. The two tissue compartments containing Sox10 + cells in the surrounding of taste buds include the connective tissue core of taste papillae and von Ebner's glands (vEGs) that are connected to the trench of circumvallate and foliate papillae. Here we present data to support that it is the vEGs, not connective tissue core, that serve as the niche of Sox10 + taste bud progenitors. In this study, we performed single cell RNA-sequencing of the epithelium of Sox10-Cre/tdT mouse circumvallate/vEG complex and used inducible Cre mouse models to map the cell lineages of vEGs and/or connective tissue (including stromal and Schwann cells). Transcriptomic analysis indicated that Sox10 expression was enriched in the cell clusters of vEG ducts that contained abundant proliferating cells, while Sox10-Cre/tdT expression was enriched in type-III taste bud cells and vEG ductal cells. In vivo lineage mapping showed that the traced cells were distributed in circumvallate taste buds concurrently with those in the vEGs, but not in the connective tissue. Moreover, multiple genes encoding pathogen receptors were enriched in the vEG ducts hosting Sox10 + cells. If this is also true in humans, our data indicates that vEG duct is a source of Sox10 + taste bud progenitors and susceptible to pathogen infections.